Uji in vitro Aktivitas Antibakteri Minyak Atsiri Batang Sereh (Cymbopogon citratus) terhadap Shigella dysenteriae - Yunita Wulansari; Enny Suswati; Septa Surya Wahyudi (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Shigella dysenteriae is bacteria that caused diarrhea with high morbidity and mortality. Resistance and toxicity has reported in some antibiotics therapy towards S. dysentriae. Therefore, alternative therapy based on herbal plants is needed. Chymbopogon citratus oil can be used as an antibacterial to Escherichia coli, Klebsiella pneumoniae, Streptococcus mutans, all strains Staphlylococcus sp, Bacillus cereus and Bacillus subtilis. This study aimed to investigate antibacterial activity of C. citratus oils on the growth of S. dysentriae and its minimum inhibitory concentration (MIC). This type of research was a quasi experimental. Antibacterial activity test performed by diffusion method. Subjects in this study were S. dysentriae. C. citratus oil concentration used were 15 μl/ml, 20 μl/ml, 25 μl/ml, 30 μl/ml, 35 μl/ml and 40 μl/ml. Positive control group was given ciprofloxacin 5 μl/ml and a negative control group was given tween-80. Inhibition zone was observed at a concentration of 25 µl/ml (P3). The MIC of C. citratus oils againts S. dysentriae was at a concentration of 25 µl/ml. Kruskal Wallis analysis showed that p=0.000 and α=0.05, it was revealed that there were differences between antibacterial activity amoung tested group with different concentration. Keywords: Shigella dysenteriae, Chymbopogon citratus oil, antibacterial